The Shortage of Malaysian Stem Cell Ethics in Mainstream Database: a Preliminary Study - Gopalan, Nishakanthi (Springer, 2019)
Ethics is a philosophical branch of inquiry that reasons between what is right and wrong. The moral philosophy of Socrates, Aristotle, and Plato from ancient Greek became the basis of most of the western ethics. These days, ethics can be divided based on its inquiries for example, normative, descriptive, metaethics, and applied ethics or based on its theories like utilitarianism, emotivism, and universal ethics. In context with applied ethics that examines issues involving emerging technologies, this study will look into the ethics of Malaysian stem cell technology based on written literature. It was mainly to identify Malaysian literature on stem cell ethics through conventional search since the mainstream international database indicated an obvious shortage. The critical review of this literature will facilitate in the understanding of unique position of Malaysia towards stem cell and its ethics in reference to the limited number. Despite the limitation, this can be a preliminary study urging for more inquiries and exploration to fulfil the multiple perspectives in ethics such as the diversity of Malaysian ethics, the impact of ethics in stem cell regulation in Malaysia, and if western contemporary ethics influences Malaysian ethics particularly involving stem cell technology. © 2019, National University of Singapore and Springer Nature Singapore Pte Ltd.